Análise da distribuição da frequência de polimorfismos em genes relógio, nos grupos étnicos asiático e caucasiano que compõem a população brasileira - Barbosa, Ana Alves [UNIFESP] (2010)
The Period 3 and Clock genes are important components of the mammalian molecular circadian system. Studies have shown association between polymorphisms in these clock genes and circadian phenotypes in different populations. Nevertheless, differences in the pattern of allele frequency and genotyping distribution are systematically observed in studies with different ethnic groups. To investigate and compare the pattern of distribution in a sample of Asian and Caucasian populations living in Brazil, we evaluated two well-studied polymorphisms in the clock genes: a variable number of tandem repeats (VNTR) in PER3 and a single nucleotide polymorphism (SNP) in CLOCK. The aim of this investigation was to search for clues about human evolutionary processes related to circadian rhythms. We selected 109 Asian and 135 Caucasian descendants. The frequencies of the shorter allele (4 repeats) in the PER3 gene and the T allele in the CLOCK gene among Asians (0.86 and 0.84, respectively) were significantly higher than among Caucasians (0.69 and 0.71, respectively). Our results directly confirmed the different distribution of these polymorphisms between the Asian and Caucasian ethnic groups. Given the genetic differences found between groups, two points became evident: first, ethnic variations may have implications for the interpretation of results in circadian rhythm association studies, and second, the question may be raised about which evolutionary conditions shaped these genetic clock variations.